PELAKSANAAN GANTI RUGI PENGADAAN TANAH PADA BENDUNGAN NIPA-NIPA DI KABUPATEN GOWA: IMPLEMENTATION OF LAND PROCUREMENT COMPENSATION ON NIPA-NIPA DAM IN GOWA DISTRICT - Tenriawati, Andi Besse; Makkawaru, Zulkifli; Tira, Andi (Faculty Of Law Bosowa University, 2021)
This study aims to determine and analyze the obstacles in the implementation of compensation payments on land acquisition for the Nipa-Nipa’s Dam in Gowa Regency and toafind out and analyze the howathe problem of compensation for land acquisition for the Nipa-Nipa Dam in Gowa can be solved. The research method used is an empirical-normative research method, which is field data as the main data source such as the results of interviews and observations. The results of the study indicate in the implementation of compensation payments on land acquisition at the Nipa-Nipa Dam in Gowa Regency, the obstacles are, the occurrence of free buying and selling of land, the existence of absentee/guntai land ownership, and not agreeing with the price offered. compensation for land acquisition for the Nipa-Nipa Dam in Gowa Regency, namely, the active role of the land acquisition committee in conducting consensus deliberation, mediation and persuasive approaches, understanding and understanding of the social function of land. The Central and Regional Governments, especially the Gowa Regency land office, should be obliged to provide an in-depth understanding of land acquisition through legal counseling, especially land law (Agrarian) both to sub-district, village/kelurahan government officials, as well as leaders and the community intensively so that better implementation in the future. People whose land is affected by the construction of the Nipa-Nipa Dam in Gowa Regency have a better understanding of the social functions of land, so that they do not ask for such high compensation so that land acquisition for the construction of the Nipa-Nipa dam can be completed.